CAREER PATH SYSTEM STRUCTURAL LECTURERIN PRIVATE UNIVERSITIES IN BANDAR LAMPUNG - Anggalia Wibasuri; Abdi Darmawan; Dona Yuliawati (Prosiding International conference on Information Technology and Business (ICITB), 2016)
Lecturer is one of the essential components of a system in higher education. Lecturers have a role, duties and responsibilities in realizing the goal of national education. So that the lecturer is the most important component in the college. The main task is Tridarma college lecturers are arranged in standard faculty workload. career systems lecturer in private universities is not only contained in the Act's regulations No. 14 2015 on teachers and lecturers. professional development of lecturers through functional or academic position, while career development in a structural position of secretary courses starting up the post of rector. For private colleges in the determination of structural positions is done without seeing the competency of a person to be served, but it generally is someone who has an emotional connection, meaning not based on seniority, rank, and functional academics. Based on this, we need a system of career paths / career path for lecturers in a structural position to be more focused and measurable so that governance and academic atmosphere in the college better. KEYWORDS: Competence Lecturer, Lecturer Performance, Promotions Department.